Human Nature and Calamities According to the Interpretation of M. Quraish Shihab (Thematic Interpretation Study of Tafsir Al-Misbah) - Azmi Abdillah Agustian; Ahmad Isnaeni; Budimansyah (al-Afkar, Journal For Islamic Studies, 2025)
This research discusses human nature and disasters and the phenomenon of disasters. As the news of disasters that hit almost every region in the world, including Indonesia, was widely reported, and how these topics were discussed. The method in this research is library research, for which the author carries out the steps of identification, collection, processing and study of existing data related to the problem of the kauniyyyah verse, both in the form of primary data and secondary data accurately and factually. Meanwhile, the secondary data referred to is other literature in the form of books, research results and other articles which are of course related to the issue of the correlation between human nature and disasters in the Al-Qur'an and Tafsir Al-Misbah. The study concludes that the Qur'an describes disasters using various terms, highlighting that these calamities are not solely decreed by Allah SWT but also linked to human behavior. The Qur'an identifies human actions such as environmental degradation, denial of faith, injustice, immorality, and hedonism as causes of disasters. While humans contribute to causing disasters, they also have the ability to prevent and respond to them through certain actions, introspection, and remembering Allah SWT. The Qur'an depicts different human reactions to disasters based on their character and emphasizes that despite the negative impacts, disasters offer lessons for future human behavior if approached with reason and clear thinking.